EBCOG position statement about the use of herbal medication during pregnancy. (January 2020) - Savona-Ventura, Charles; Mahmood, Tahir
Abstract: Pregnant women often resort to herbal medication to ameliorate the disturbing symptoms associated with pregnancy in the mistaken belief that these are safe and carry no potential harmful effects to the developing fetus. Healthcare personnel must be cognizant of the potential adverse side effects of these substances to be able to better advise their patients.